Gerakan Millenarian di Pegunungan Gawalise Palu Pasca Kemerdekaan - Sairin, Mohammad (Perkumpulan Program Studi Sejarah Se-Indonesia, 2024)
This paper discusses two millenarian movements in the Gawalise Mountains region of Central Sulawesi that emerged in the post-independence era of Indonesia, namely the Panteuwa Movement, which occurred in 1952, and the Madi Movement, which occurred in 2005. This paper uses the historical method, which consists of four stages: heuristics, verification, interpretation, and historiography. The sources used include the Sulawesi Provincial Secret Archives collection obtained from the South Sulawesi Provincial Library and Archives Office in Makassar. This paper reveals that the movement carried out by Panteuwa alias Salamagawu and Arifin alias Madi was a millenarian movement, which “pointed to a golden age that said that all injustice would be ended and harmony would be restored.” Both Panteuwa alias Salamagawu’s teachings and Madi’s teachings have various elements in them, such as nativism (indigenous), millenarianism, messianism (saviour), and revivalism.